Perencanaan dan Pengendalian Persediaan Bahan Baku Biji Plastik Oriented Polypropylene di CV. XYZ - Adhindha Putri Mayangsari; Putu Eka Dewi Karunia Wati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
CV. XYZ is a company that produces household appliances made from Oriented Polypropylene (OPP) plastic pellets. The company is experiencing an excess of raw material inventory due to orders still being based on estimates without considering actual production needs. In 2025, the average remaining inventory reached 4,020 kg with an estimated storage cost of Rp12,288,885 per year. This condition resulted in high storage costs and inefficiencies in inventory management. This study aims to develop a production schedule using the Run Out Time (ROT) method as the basis for determining raw material needs, as well as to determine optimal inventory control using Economic Order Quantity (EOQ), safety stock, and reorder point. The research results show that the ROT scheduling produces a total of 412,508 pcs from April to June 2026. The EOQ method results in an optimal order quantity of 5,447 kg per order, a safety stock of 3,731 kg, and a reorder point of 5,091 kg. The total inventory cost using the EOQ method is Rp4,167,928, which is 31.8% lower than the company's policy of Rp6,115,000, resulting in savings of Rp1,947,072.